DINAMIKA PERUSAHAAN PELAYARAN PERNIAGAAN N.V. KONINKLIJKE PAKETVAART MAATSCHAPPIJ DI HINDIA BELANDA TAHUN 1930 1939 - Susanti, Dwi (History Department, Faculty of Humanities, University of Jember, 2024)
This article examines the operational dynamics and business strategy of N.V. Koninklijke Paketvaart Maatschappij in the Dutch East Indies during the period 1930-1939. This merchant shipping company played an important role in connecting the Dutch East Indies Islands, as well as in supporting the Dutch colonial economy. The questions tob be answered here are (1) why N.V. Koninklijke Paketvaart Maatschappij operated in the Dutch East Indies, (2) how did N.V. respond? Koninklijke Paketvaart Maatschappij towards the malaise crisis of 1930-1939, (3) what was the impact of the malaise crisis on the sustainability of N.V. Koninklijke Paketvaart Maatschappij 1930-1939. The theoretical basis used is Emile Durkheim's functional structural theory. The research method used is a historical method according to Kuntowijoyo, starting with topic selection, heuristics, source criticism, verification, interpretation and historiography. In the 1930s, N.V. Koninklijke Paketvaart Maatschappij faced various challenges, including the impact of the global economic depression. Through a study of archival documents, annual reports, and secondary literature, this research found that N.V. Koninklijke Paketvaart Maatschappij was able to survive and adapt through route diversification and support from the colonial government. N.V. Koninklijke Paketvaart Maatschappij expanded its route network to cover more ports in the Dutch East Indies and the surrounding region, as well as international routes. This diversification helps N.V. Koninklijke Paketvaart Maatschappij reduces dependence on certain routes and expands market share. N.V. Koninklijke Paketvaart Maatschappij maintained close relations with the Dutch colonial government to obtain financial support and favorable regulations. Keywords: Dutch East Indies; N.V. Koninklijke Paketvaart Maatschappij; Merchant Shipping Company.